The Electrotechnical Complex of the KTM Tokamak Pulsed Power Supply System; Physics of Atomic Nuclei; Vol. 82, iss. 7 - Zarva D. B. Denis Borisovich; Deriglazov A. A. Aleksey Alekseevich; Batyrbekov E. G. Erlan Gadletovich; Tazhibaeva I. L. Irina Lashkarovna; Pavlov V. M. Vadim Mikhailovich; Li A. M. Aleksey Mikhaylovich; Mezentsev A. A. Anton Alekseevich; Merkulov S. V. Stepan Vadimovich; Golobokov Yu. N. Yury Nikolaevich (2019, 2019)
Title screen